2021
DOI: 10.1186/s12610-020-00119-z
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic subinguinal varicocelectomy for testicular pain: a retrospective study on outcomes and predictors of pain relief

Abstract: Background Approximately 2–10% of patients with varicocele complain of pain. Varicocelectomy for testicular pain is a surgical choice when conservative therapy fails to relieve the pain. Different variables have been reported as prognostic factors for pain relief following varicocele ligation. Moreover, the success rate of varicocelectomy for testicular pain has varied among studies. This retrospective study aimed to investigate the predictors and success rate of microscopic subinguinal varicoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Thereby, the testicle weight was increased by 36%. 17 The number of spermatozoa depicted in Figure 3 (a) and their rate of motility shown in Figure 3 (b) was decreased significantly in the ND group; the WS-treated group showed significant recovery from the damage caused by ND in both the sperm count as well as their motility rate. Based on the photoactometer study observed before treatment, the physical activity was higher in the ND and the drug intervention group.…”
Section: Discussionmentioning
confidence: 87%
“…Thereby, the testicle weight was increased by 36%. 17 The number of spermatozoa depicted in Figure 3 (a) and their rate of motility shown in Figure 3 (b) was decreased significantly in the ND group; the WS-treated group showed significant recovery from the damage caused by ND in both the sperm count as well as their motility rate. Based on the photoactometer study observed before treatment, the physical activity was higher in the ND and the drug intervention group.…”
Section: Discussionmentioning
confidence: 87%
“…Park et al reported that a shorter time span from varicocele pain onset to surgery (<6 months) resulted in greater improvement in pain resolution ( p = 0.004) [ 39 ]. However, some studies revealed no significant differences between the duration of preoperative pain and pain relief [ 24 , 42 ].…”
Section: Predictors Of Treatment Outcomementioning
confidence: 99%
“…A significantly better pain relief is seen in patients with unilateral symptoms. 32 A systematic review and meta-analysis from Lundy et al found that 75%, 76%, 85%, and 90% of patients had partial or complete improvement of pain after undergoing varicocelectomy by inguinal, retroperitoneal, laparoscopic, and microsurgical approaches respectively. 33 Sheehan et al reported 50% and 89% complete pain resolution at 1-month and 1-year post varicocele treatment by embolization.…”
Section: Pain Resolutionmentioning
confidence: 99%